2019
DOI: 10.1186/s12984-019-0491-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 8 weeks of treatment with transcranial pulsed electromagnetic fields on hand tremor and inter-hand coherence in persons with Parkinson’s disease

Abstract: BackgroundParkinson’s disease (PD) tremor comprises asymmetric rest and postural tremor with unilateral onset. Tremor intensity can be amplified by stress and reduced by attention, and the medical treatment is complex. Mirror movements and unintentional synchronization of bimanual movements, possibly caused by insufficient inhibition of inter-hemispheric crosstalk, have been reported in PD, indicating a lag of lateralization.Potential neuroprotective effects of pulsed electromagnetic fields (PEMF) have been re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
0
8
0
1
Order By: Relevance
“…El tratamiento con el CEM utilizado en nuestro estudio, parece compensar esa deficiencia dopaminérgica y permitir mantener una mejoría en el equilibrio. Además, los tratamientos electromagnéticos en pacientes con la EP han mostrado una mejora en el temblor postural (Malling et al, 2019) y otros síntomas motores (Liu, Wang, He & Ye, 2008).…”
Section: Discussionunclassified
“…El tratamiento con el CEM utilizado en nuestro estudio, parece compensar esa deficiencia dopaminérgica y permitir mantener una mejoría en el equilibrio. Además, los tratamientos electromagnéticos en pacientes con la EP han mostrado una mejora en el temblor postural (Malling et al, 2019) y otros síntomas motores (Liu, Wang, He & Ye, 2008).…”
Section: Discussionunclassified
“…The present study includes baseline accelerometer data sampled during a rest and a postural condition from a subsample of persons diagnosed with idiopathic PD (PD-group) participating in a double-blinded randomized clinical trial [811] (clinicaltrials.gov NCT02125032) along with data from an age and sex matched healthy reference group without visible tremor (REF-group) [8, 11, 12]. Inclusion criteria for the trial were an unchanged and optimal medical treatment regarding PD 6 weeks prior to participation; Mini Mental State Examination score > 22; and age > 18 years.…”
Section: Methodsmentioning
confidence: 99%
“…Exclusion criteria were any known neuromuscular or neurological disease other than PD that might interfere with motor function; psychopathological treatment of other conditions than depression; substance abuse; and active medical implants. The REF-group was included to determine pathologic tremor threshold values defined as mean tremor intensity + 2 SD of the REF-group (rest: 0.300 m/s 2 , postural: 0.783 m/s 2 ) [11] and to gain a reference pattern of time-dependency of movements in the two conditions. Fifty persons with PD had at least one tremoring hand and were included in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study focused on non-invasive functional effect measures and was the first to apply T-PEMF in PD. We found that 30-min daily treatment with T-PEMF over eight weeks were superior to placebo treatment to increase functional rate of force development during a cyclic chair rise task, and that inter-hand coherence was reduced in the least affected patients with PD [ 15 , 17 ]. However, structural changes in the brain take time and eight weeks of treatment is unlikely to be sufficient.…”
Section: Introductionmentioning
confidence: 99%